Heme Oxygenase-1-Targeted Cancer Therapy: At the Crossroads of Cytoprotection and Tumour Progression - Raeispour, Marzieh; Murias, Marek (Journal of Medical Science, 2025)
Introduction. HO-1 is a stress-responsive enzyme involved in cellular protection against oxidative damage, inflammation, and tissue injury. However, in cancer, its cytoprotective functions may paradoxically support cancer progression, immune evasion, and therapy resistance. Material and methods. This review explores current findings on HO-1’s dual role in cancer biology. We analysed studies addressing its function in redox regulation, angiogenesis, immune modulation, iron metabolism, and its impact on treatment response. Particular focus was placed on HO-1’s downstream metabolites (CO, biliverdin/bilirubin, and iron) and their influence on tumour development. Results. HO-1 contributes to cellular defence by limiting reactive oxygen species and supporting DNA repair. However, its overexpression in tumours promotes survival signalling, angiogenesis (via VEGF and HIF-1α), metabolic reprogramming, and resistance to apoptosis and chemotherapy. Additionally, HO-1 regulates ferroptosis by modulating intracellular iron and lipid peroxidation. The Nrf2/HO-1 axis is frequently upregulated in tumours, enhancing antioxidant capacity and undermining therapeutic efficacy. Preclinical studies show that HO-1 inhibition—via gene silencing, small molecules, or combination with chemotherapy and photodynamic therapy—can restore treatment sensitivity and suppress tumour growth. Conclusions. HO-1 plays a context-dependent, dual role in cancer as both a protector and promoter. Therapeutic targeting of HO-1 holds promise but requires precision to avoid disrupting its protective roles in normal tissues. Further research should aim to develop selective, tumour-specific HO-1 inhibitors and integrate them into combination treatment strategies.